Strategi Guru Dalam Pembelajaran Aqidah Akhlak - Ulil Uyunin Nuhiyah; Rahmat Rahmat (Pedir Research Institute, 2023)
This research was taken place in MI Al Hidayah Trowulan which aims to determine the teacher's Strategy in Learning Aqidah Akhlak at MI Al Hidayah Trowulan Trowulan District and knowing the Implications of Teacher's Strategies in Learning Aqidah Akhlak at MI Al Hidayah Trowulan Trowulan District. The study used qualitative methods with data collection techniques of participation observation, interviews, and documentation. Sources of data in this study were the strategy, learning, and Aqidah Akhlaq. To check the validity of the data, researchers used triangulation. The results of this study indicate, 1) The Teacher's Strategies in Learning Aqidah Akhlak at MI Al Hidayah Trowulan were: Responsibility, Discipline, Discussion, Creativity, Innovativeness, Making learning tools, Collaboration, Preparing data collection administration, Aqidah Akhlak teachers applying learning strategies so that students more easily grasped, understand, understand, and practice, and use the strategies that have been prepared 2) The implications of Teacher Strategy in Learning Aqidah Akhlak at MI Al Hidayah Trowulan, namely Learning to be Effective, Competence or learning objectives are achieved, Support, motivation and collaboration so that learning objectives are achieved, Living and practicing Islamic teachings about morals, Living and believing with the right beliefs, Understanding and understand commendable morals and stay away from despicable morals, Improving the quality of learning, Improving students' affective, cognitive and psychomotor abilities, and In Aqidah Akhlak learning strategies students are able to practice commendable morals, and Worship becomes active and istiqomah, sorting and choosing relationships.